(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper explores how faculty in Kazakhstan perceive the current and potential effects of the Russia-Ukraine war and sanctions on internationalization and international mobility in higher education in the Central Asian country. The purpose of the study was to provide some initial insights into the perceived effects of the conflict on international mobility and higher education in the country, which has the longest border with Russia. The study uses grounded theory as an approach to research design. The data was collected via semi-structured interviews whereby the participants were selected from among faculty of Kazakhstani universities using a combination of snowball and maximal-variation sampling approaches. The results of the analysis revealed that the participants interpret the impacts of the conflict predominantly in neoliberal terms with only some faculty members noting potential effects in terms of academic colonialism. Identified themes are best interpreted in terms of the conceptual construct of capital. We suggest a combination of several capital theories as a potential theoretical framework for understanding perceptions of the effects of war on internationalization and international mobility in higher education.